ANALISIS DATA ANGIN PERMUKAAN DI BANDARA PANGKALPINANG MENGGUNAKAN METODE WINDROSE - Fadholi, Akhmad (Jurnal Geografi : Media Informasi Pengembangan dan Profesi Kegeografian, 2013)
In flight operation, there are three popular term which are take off, cruising andlanding. Within flight safety, landing is the most crusial phase, one ofmeteorology factor which has intensive effect is runway surface wind. A researchabout wind data analysis is used for determining existence pattern. In DepatiAmir Airport, Pangkalpinang conducted a research of wind data analysis to showrunway surface wind pattern in order to reduce flight accident potential. Theresearch’s result which analyzed used wind rose method and data range between2000 to 2012, showed that the dominant surface wind of Depati Amir Airportalmost during a year flew from 135 to 1650 (South-East) with 1 - 4 knotacceleration. Although, in November until April various wind is high. Beside that,from the morning to afternoon, the dominant surface wind flew from East andfrom afternoon to night the surface wind flew from South-East.